Indoxacarb: a novel oxadiazine insecticide for management of tomato fruit borer, Helicoverpa armigera - Sharma et al, Smriti (Indian Journal of Plant Protection, 2018)
Tomato fruit borer,Helicoverpa armigerais the key pest of tomato causing substantial losses in fruit yield necessitating plant protection measures for economic benefts. Indoxacarb 14.5 SC, a reduced-risk insecticide belonging to oxadiazine group, was evaluated for three years in comparison with ﬂubendiamide 480 SC and profenophos 50 EC and an untreated control for the management of this pest. All the insecticides proved signifcantly better than untreated control in managing the damage caused by H. armigera on tomato crop. The second application of indoxacarb 14.5 SC @ 500 ml/ha decreased the larval population per plant (0.6 larva/ plant) after 3 days of spray. The pooled data on per cent fruit infestation after 3 days of spray were signifcantly lower in indoxacarb 14.5 SC @ 500 ml/ha (7.1) and was at par with indoxacarb 14.5 SC @ 375 ml/ha (9.1), ﬂubendiamide 480 SC @ 75 ml/ha (7.2) and profenophos 50EC @ 1500 ml/ha (7.9). Present studies revealed that indoxacarb 14.5 SC @ 500 ml/ha treatment gave signifcantly higher yield of 644.2 q/ha followed by ﬂubendiamide 480 SC @ 75 ml/ha (626.0 q/ha). Hence, the present study showed that indoxacarb 14.5 SC @ 500 ml/ha can give effective management of tomato fruit borer in terms of decreased larval population, and fruit damage with a concomitant increase in yield and can be used in rotation with other pesticides for developing an effective fruit borer management strategy in tomato.